Observation of a new baryon state in the Λ0bπ+π- mass spectrum - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Journal of high energy physics, 2020)
A new baryon state is observed in the Lambda(0)(b)pi(+)pi(-) mass spectrum with high significance using a data sample of pp collisions, collected with the LHCb detector at centre-of-mass energies root s = 7, 8 and 13 TeV, corresponding to an integrated luminosity of 9 fb(-1). The mass and natural width of the new state are measured to be m = 6072.3 +/- 2.9 +/- 0.6 +/- 0.2 MeV, Gamma = 72 +/- 11 +/- 2 MeV, where the first uncertainty is statistical and the second systematic. The third uncertainty for the mass is due to imprecise knowledge of the Lambda(0)(b) baryon mass. The new state is consistent with the first radial excitation of the Lambda(0)(b) baryon, the Lambda(b)(2S)(0) resonance. Updated measurements of the masses and the upper limits on the natural widths of the previously observed Lambda(b)(5912)(0) and Lambda(b)(5920)(0) states are also reported.
Gesehen am 22.10.2020
Im Titel sind das Plus- und Minuszeichen hochgestellt
Im Titel ist "0" hochgestellt, "b" tiefgestellt
LHCb Collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, S. Braun, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, R. Kopecna, B. Leverington, J. Marks, S. Neubert, A. Piucci, N. Skidmore, S. Stemmle, U. Uwer, A. Zhelezov [und 822 weitere]